Applications of Natural and Synthetic Melanins as Biosorbents and Adhesive Coatings - Park, Seo A.; Lee, Changgu; Lee, Jechan; Jung, Seungho; Choi, Kwon Young (Biotechnology and Bioprocess Engineering, 2020)
Natural and synthetic melanins are promising pigments for several uses, such as biosorbents and bioadhesives. Further, their high biocompatibilities and excellent biological activities potentially allow them to be ideal biomaterials for environmental and biotechnological applications. Naturally occurring melanin has been used as a biosorbent for the environmental treatment of organic chemicals and for metal ion removal, and melanins have been chemically engineered to function more efficiently. In addition, melanin has been engineered for use as an adhesive coating material, and its polymeric properties have been enhanced for medical applications. Clearly, given melanin’s high biocompatibility and biodegradability, it is a very viable biopolymer for further applications in environmental biotechnology fields. In this review, we highlight the uses of melanin as a biosorbent and bioadhesive in biotechnology fields.
Keywords: Adhesive coatings; Bio adhesives; Biosorbents; Biotechnological applications; Environmental biotechnology; Environmental treatment; Metal ion removal; Naturally occurring; bioadhesive; biocompatibility; biosorption; melanin; pigment